Exploring the Relationship between Temperament and Preferred Playing Positions Among Soccer Athletes - Simon, John Enokela; Uzoigwe, Tobechi Larry (JSES : Journal of Sport and Exercise Science, 2026)
Purpose: This study investigates the connection between an athlete's temperament and their preferred soccer playing positions, concentrating on personality traits like introversion, extroversion, neuroticism, and traditional temperament types (melancholic, phlegmatic, choleric, sanguine). Materials and Methods: Conducted among soccer players at Nasarawa State University, Keffi, Nigeria, the research employs a cross-sectional quantitative design. A total of 98 male athletes, selected through purposive sampling, participated in the Vice-Chancellor's soccer competition in 2022. Their preferred positions were classified into central and side roles. Result: Results from hypothesis testing indicated a statistically significant relationship between introversion/extroversion and playing position (χ2 = 5.26, p = 0.02). Notably, 86.4% of introverts opted for central positions, compared to 66.7% of extroverts. In contrast, neuroticism did not significantly impact position preference (χ2 = 0.18, p = 0.67). Additionally, a strong relationship was found between personality temperament and playing position (χ2 = 19.56, p = 0.003). Phlegmatic and choleric individuals were more inclined to occupy midfield roles, while melancholic and phlegmatic players were primarily in defense, and attackers tended to have melancholic and sanguine traits. Conclusion: These findings suggest that personality traits have a notable influence on playing position preferences in soccer, offering useful insights for coaches and sports psychologists regarding player selection and team dynamics. Future research might explore other psychological and physiological factors affecting position choices in competitive soccer.